Strength and Absorption of Sorghum Husk Ash Sandcrete Blocks8 (2020)
Sorghum husk is one of the main agricultural wastes in milling processes that is available in large quantity in Nigeria. The available methods of handling sorghum husk have serious health and environmental implications. Hence, there is need for proper disposal of this agricultural waste. The chemical compositions of Sorghum Husk Ash (SHA) were determined using X-ray fluorescence analyzer. Production of sandcrete blocks by incorporating SHA as partial replacement for cement was investigated. SHA replacement levels of 1, 2, 3, 4 and 5% were used. A total of 54 hollow block specimens of dimension 450 × 225 × 225 mm were cast to undergo density, water absorption and compressive strength tests at 7, 14, and 28 days of curing respectively. Results revealed that percentage sum of silica, alumina and ferric oxide contents was 77.3% which exceeds 70% specified limit by ASTM C 618 for pozzolanic material categorization. The results also indicate that increase in SHA replacement (0 - 5%) led to decrease in density (2273.8 - 2185.4 kg/m3) and increase in water absorption (6.1 – 9.2%). The 28 day compressive strength increased by 1.5, 7.3, 20.8, 5.2 and 6.7% for 1, 2, 3, 4 and 5% SHA replacement respectively. It is concluded that SHA is a good pozzolan and can be used to improve the compressive strength of sandcrete blocks at satisfactory density and water absorption.